Alimentación, comportamiento de oviposición, ciclo de vida y enemigos naturales de Hamadryas feronia (Nymphalidae) en la Amazonía del Perú - Vásquez-Bardales, Joel (Universidad de Costa Rica, 2021)
Introduction: Hamadryas feronia feronia, which mimics the bark of trees and often makes attention-grabbing sounds when flying, has good potential for bio-business (export, handicrafts and tourist breeding centers). However, its biological aspects are still unknown, which hinder its captive breeding. Objectives: To determine the biological aspects of feeding, oviposition behavior, life cycle and natural enemies of Hamadryas feronia feronia L. in San Rafael-Indiana, Loreto, Peru. Methods: Sampling was conducted from January 2018 to December 2019 in the community of San Rafael, Amazon River. Adults were observed during the day, their food plants, oviposition behavior, biological cycle and natural enemies were recorded. The life cycle was evaluated in the laboratory, using 20 eggs recently deposited on the leaves of their host plant. Results: The larvae of H. feronia feronia feed on the leaves of Dalechampia juruana and the adults feed on the bark sap of Cedrela odorata, Spondias mombin, Uncaria guianensis and the fermented fruits of Syzygium malaccense and Pouteria caimito. Adults fly on sunny days, males emit a loud sound when flying. Females prior to oviposition flit irregularly around their host plant between 8.00 and 14.00 h and deposit their eggs on the upper and underside of leaves in isolation, most frequently on the underside. The duration of the cycle from egg to adult was 28.24 days. The average egg period was 3.75 ± 0.40 days. The larvae passed through five larval instars: the first instar 3.21 ± 1.03 days, the second 2.78 ± 0.73 days, the third 2.67 ± 0.77 days, the fourth 3.22 ± 0.81 days, and the fifth 4.61 ± 0.70 days. The prepupal period lasted 1.33 ± 0.49 days and the pupal period 6.67 ± 0.80 days; the adults hatched between 10:00 to 11:00 h. Adult males lived on average 31.80 ± 3.29 days, the female 42.00 ± 2.14 days and their eggs were parasitized by a microhymenopteran (Scelionidae). Conclusions: This study allowed to know the biological aspects of H. feronia feronia identifying its food plants of both larvae and adults, its oviposition behavior, as well as it has been determined that it has a relatively short biological cycle with a period of less than one month and its eggs are consumed by a small Hymenoptera that can hinder its production. This work provides necessary information to develop the breeding of H. feronia feronia, oriented to its conservation, environmental education and biotrade (tourism and handicrafts) in the Peruvian Amazon.